8-(N,N-diethylamino)-n-octyl-3,4,5-trimethoxybenzoate reduced [Ca2+]i elevation induced by histamine, serotonin, and glutamate in cultured calf basilar artery smooth muscle cells - Wang Bin; Zhang Xiao-Qing; Liu Tian-Pei; Xiao Ji-Gao (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of 8-(N,N-diethylamino)-n-octyl-3,4,5- trimethoxybenzoate (TMB-8) on intracellular free calcium ([Ca2+]i) in cultured calf basilar artery smooth muscle cells. METHODS: [Ca2+]i was examined by a system of measurement of AR-CM-MIC, using Fura 2-AM as a fluorescent indicator. RESULTS: In the presence of extracellular Ca2+ 1.3 mmol.L-1, histamine (His), serotonin (5-HT), and sodium glutamate (Glu) markedly increased the [Ca2+]i which was attenuated by TMB-8. In Ca2+ free Hanks' solution containing egtazic acid 0.1 mmol.L-1, TMB-8 not only reduced the resting [Ca2+]i, but also inhibited the elevation of [Ca2+]i evoked by His and 5-HT. CONCLUSION: TMB-8 reduced the resting [Ca2+]i and attenuated His-, 5-HT-, and Glu-induced increases of [Ca2+]i in basilar artery smooth muscle cells.